W Sprawie Obliczania Mostów Zakrzywionych o Przekroju Otwartym - Dąbrowski, R. (Engineering Transactions, 1957)
In this paper, a simplified derivation of equation for bending moments and shearing forces is proposed for the outer and the inner girder of a curved bridge with open cross-section, by resolving the load with an arbitrary force P into two component loads: (1) the load by the force P passing through the centre of curvature and, (2), the load by the moment M = Pr acting in the radial plane, where r is the distance of the force from the centre of curvature. In the solution for a multi-spam system, additional moments are introduced at the supports.